The effectiveness of sub-degree programmes the associate degree programme: a study of graduates' preparedness for further study and employment - Chan, Kwai Chi Amy (2019)
The expansion of post-secondary education in Hong Kong triggered the establishment of community colleges for the purpose of widening access to post-secondary education and enhancing the employability of graduates. Although the community colleges established in Hong Kong offer associate degree (AD) programmes, their subsequent educational value is still not evident. This study investigates how effective AD curricula are in enabling graduates to achieve competencies in generic skills necessary for further study and employment. The study employs a case study design and uses both qualitative and quantitative research methods to explore graduates’ perceptions about the usefulness of AD programmes in preparing students for further study and employment. The research questions are: What motivates AD graduates to pursue further study? What perceptions do graduates have about the usefulness of AD programmes in enabling them to pursue further study and acquire employment? Does the AD curriculum enable students to acquire basic competency in generic skills essential for further study and employment? One hundred and six AD graduates were involved in the study. All qualitative data were analysed using coding strategy, and all quantitative results using SPSS version 16.